Penetrating neck trauma in children: An uncommon entity described using the National Trauma Data Bank. Issue 4 (April 2016) - Stone, Melvin Eugene; Farber, Benjamin A.; Olorunfemi, Odunayo; Kalata, Stanley; Meltzer, James A.; Chao, Edward; Reddy, Srinivas H.; Teperman, Sheldon
Abstract : BACKGROUND: Penetrating neck trauma is uncommon in children; consequently, data describing epidemiology, injury pattern, and management are sparse. The aim of this study was to use the National Trauma Data Bank (NTDB) to describe pediatric penetrating neck trauma (PPNT). METHODS: The NTDB was queried for children (defined as <15 years old) with PPNT between years 2008 and 2012. Descriptive analysis was used to describe age groups (0–5, 6–10, and 11–14 years) and injury type categorized as aerodigestive, vascular, cervical spine, and nerve. RESULTS: A total of 1, 238 patients with penetrating neck trauma were identified among 434, 788 children in the NTDB (0.28%). Mean age was 7.9 years, and 70.6% of patients were male. The most common mechanisms of injury were stabbing (44%) and gunshot/firearm (24%). Most patients were treated at a pediatric trauma center (65.8%). Computed tomographic scan was the most frequent (42.2%) diagnostic study performed, followed by laryngoscopy (27.0%) and esophagoscopy (27.4%). Almost a quarter of patients (23.7%) went directly to the operating room from the emergency department (ED). Aerodigestive injuries were most common and occurred more frequently in the youngest age group ( p < 0.001). Operative procedures for aerodigestive type injuries were most common (82.7%). There were 69 deaths, yielding a mortality rate of 5.6%. When adjusting for age, admission to a pediatric trauma center, and injury type, only vascular injury (odds ratio, 3.92; 95% confidence interval, 2.19–7.24; p < 0.0001) and ED hypotension (odds ratio, 27.12; 95% confidence interval, 15.11–48.67; p < 0.0001) were found to be independently associated with death. CONCLUSION: PPNT is extremely rare—0.28% reported NTDB incidence. Age seems to influence injury type but does not affect mortality. Computed tomographic scan is the dominant diagnostic study used for selective management. Vascular injury type and hypotension on presentation to the ED were independently associated with mortality. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.